PsycEXTRA Dataset 2002
DOI: 10.1037/e437862005-001
|View full text |Cite
|
Sign up to set email alerts
|

Substance Dependence, Abuse, and Treatment: Findings from the 2000 National Household Survey on Drug Abuse

Abstract: This report provides the first information on substance dependence, abuse, and treatment obtained from the 2000 National Household Survey on Drug Abuse (NHSDA), a project of the Substance Abuse and Mental Health Services Administration (SAMHSA). Because of major changes to the NHSDA and the definition for measuring treatment need, these estimates cannot and should not be compared with estimates from previous years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 4 publications
0
35
0
Order By: Relevance
“…Keeping in mind that this is a conservative estimate of the provincial level of need for cannabis treatment, as it does not adequately take into account all individuals experiencing cannabis-related problems, there is a potentially large unrecognized and unmet need for cannabis treatment. Data from the 2000 NHSDA suggest that only about one-quarter of those in need in the USA received cannabis treatment [9] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keeping in mind that this is a conservative estimate of the provincial level of need for cannabis treatment, as it does not adequately take into account all individuals experiencing cannabis-related problems, there is a potentially large unrecognized and unmet need for cannabis treatment. Data from the 2000 NHSDA suggest that only about one-quarter of those in need in the USA received cannabis treatment [9] .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing cannabis-related problems appears to be inversely related to age, such that adolescents and young adults are more prone to cannabis dependence than are adults [1] . For instance, the rate of cannabis use disorders is estimated at over 3% of adolescents and 4% of young adults in the USA [9] . This is concerning given evidence that the age of fi rst use of cannabis decreased steadily through the latter half of the last century [1,10] , and that the rate of past-year cannabis use among adolescents increased through the 1990s in many countries [11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distinction is particularly important given the significant unmet need for adolescent AOD treatment. Using a nationally representative sample, the National Survey on Drug Use and Health (NSDUH) 2000 found that only 11.4% of 12-to 17-year-olds who needed treatment for illicit drug addiction received treatment (Epstein, 2002). Adolescent AOD treatment research usually recruits samples from treatment facilities.…”
Section: Adolescent Factors Associated With Access To Treatmentmentioning
confidence: 99%
“…However, these rates do not consider the unmet need. Data from the 2000 National Household Survey in the United States suggest that approximately only one quarter of those in need received cannabis treatment (Epstein, 2002).…”
Section: Introductionmentioning
confidence: 99%